Thermal behaviour of nitrogen oxides relevant to oxidative denitrogenation. (September 2019) - Mirshamsi, Sepideh; Yan, Yuwei; Kamal, Sidra; Yasemi, Amir-Arsalan; Gupta, Rajender; de Klerk, Arno; Prado, Glaucia H.C.
Highlights: Solid-liquid phase transition data of nitrogen oxides was determined by Differential Scanning Calorimetry. Some of the nitrogen oxides studied evaporated at atmospheric pressure. Some of the nitrogen oxides studied decomposed at atmospheric pressure. All nitrogen oxides studied decomposed in the liquid phase. Pyrolysis of the nitrogen oxides studied did not release nitrogen as NOx . Abstract: Nitrogen compounds in crude oil are known to cause several problems during refining including catalyst deactivation and gum formation. Industrially, nitrogen is removed by hydro-treating, which requires ring saturation prior to denitrogenation and makes hydro-treating an expensive process for heavy crude oils or coal liquids with high nitrogen content. Oxidative denitrogenation is an alternative method to hydro-treating, where the nitrogen compounds are oxidized to form nitrogen oxides, which can be separated from the oil by extraction with a polar solvent. During this separation process there is a loss of hydrocarbon material which can be between (10–20) wt% for an oil containing 1 wt% of N. The possibility to release nitrogen as NOx by thermal treatment and consequently recover the hydrocarbon portion from the N-oxide molecule is the topic explored in this work. The thermochemistry of the N-oxides of pyridine, 3-picoline, 2-mercaptopyridine, quinoline, 4-nitropyridine, 3, 5-dimethylpyridine, picolinic acid, 4-picoline, 3-hydroxypyridine, nicotinic acid, isonicotinic acid, and nicotinamide was studied. The results showed that the N-oxides of pyridine and 3-picoline evaporated at atmospheric pressure while the other compounds decomposed after or during melting or during evaporation. Decomposition temperatures could be determined for all the N-oxides during thermal analysis at 5 MPa gauge. Infra-red spectroscopy of the residues after thermal treatment indicated that the compounds still contained nitrogen. The suggested chemistry taking place upon thermal decomposition in the liquid phase was discussed. N-oxides may form an oxaziridine intermediate, which results in formation of polymeric structures that still contain the nitrogen. Therefore, pyrolysis of the N-oxides subsequent to oxidation seems to be inefficient to liberate the nitrogen as NOx .